2008
DOI: 10.1177/193229680800200314
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-Based Non-Clinical Comparison of Occlusion Rates Using Three Rapid-Acting Insulin Analogs in Continuous Subcutaneous Insulin Infusion Catheters Using Low Flow Rates

Abstract: During CSII under laboratory conditions, early catheter occlusions (within 72 hours) are rare and independent of the choice of insulin analog. For patients using insulin pump therapy, the importance of catheter change within 72 hours should be emphasized irrespective of the insulin used. Beyond 72 hours, the risk of occlusion differs between insulins, being more common with glulisine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 9 publications
2
49
0
Order By: Relevance
“…There was no single specific event related to an extended catheter use but events of all kinds and nature occurred after day 3, including but not limited to pulling out, kinking, adhesive getting loose, leakage of insulin from the infusion set or the infusion site, and signals of skin irritation, such as bruising, redness, or swelling. Even when the patients locally tolerated a longer use of the infusion sets at the infusion site for up to 7 days, there appeared to be changes in the insulin absorption leading to a slow but steady loss in glycemic control with increased duration of use, as indicated by a steady increase in mean daily blood glucose concentrations, which is in line with a most recent observational study by Perrin et al 11,12 In general, potential problems that may occur in adult and adolescent patients when using the infusion sets longer than the recommended 48-72 hours may be technical problems, such as catheter occlusions or kinking, 13,14 bacterial contaminations leading to skin inflammation, [15][16][17] potential changes in physicochemical delivery characteristics, 18,19 and local skin reactions to the adhesive, resulting in redness, itching, and other symptoms of skin irritation. 12 The purpose of this study was to evaluate the safety and efficacy of using infusion sets for 2 days versus 4 days during a period of 3 months each in a prospective and randomized crossover protocol in patients with type 1 diabetes.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…There was no single specific event related to an extended catheter use but events of all kinds and nature occurred after day 3, including but not limited to pulling out, kinking, adhesive getting loose, leakage of insulin from the infusion set or the infusion site, and signals of skin irritation, such as bruising, redness, or swelling. Even when the patients locally tolerated a longer use of the infusion sets at the infusion site for up to 7 days, there appeared to be changes in the insulin absorption leading to a slow but steady loss in glycemic control with increased duration of use, as indicated by a steady increase in mean daily blood glucose concentrations, which is in line with a most recent observational study by Perrin et al 11,12 In general, potential problems that may occur in adult and adolescent patients when using the infusion sets longer than the recommended 48-72 hours may be technical problems, such as catheter occlusions or kinking, 13,14 bacterial contaminations leading to skin inflammation, [15][16][17] potential changes in physicochemical delivery characteristics, 18,19 and local skin reactions to the adhesive, resulting in redness, itching, and other symptoms of skin irritation. 12 The purpose of this study was to evaluate the safety and efficacy of using infusion sets for 2 days versus 4 days during a period of 3 months each in a prospective and randomized crossover protocol in patients with type 1 diabetes.…”
supporting
confidence: 76%
“…The authors concluded that for patients using insulin pump therapy, the importance of catheter change within 72 hours should be emphasized irrespective of the insulin used. 13 A self-report questionnaire was used by Pickup et al to collect information about the nature of nonmetabolic complications of continuous subcutaneous insulin infusion, which was completed by 92 patients with a mean infusion set usage time of 3.2 ± 0.7 days (range 2-6 days). 21 The most common infusion set problems were kinking (64.1% of subjects) and blockage (54.3%), which was associated with >3 days of use of infusion sets plus lispro insulin in the pump.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with in vitro studies showing that beyond 3 days of infusion the probability of occlusion occurring in a catheter is greater with lispro than aspart. 12 Glulisine had the greatest risk of occluding in these in vitro studies (followed by lispro), but the number of subjects using this analog in our survey was too small to make firm conclusions about whether this insulin was associated with blockage. The short-acting analog insulins precipitate in the order of their isoelectric points, 13 so (probably) as carbon dioxide diffuses into the cannula and lowers the pH of the insulin, glulisine aggregates or precipitates first (pI approximately 6.6), followed by lispro (pI approximately 5.6) and lastly aspart (pI approximately 5.1).…”
Section: Discussionmentioning
confidence: 86%
“…The authors concluded that for patients using insulin pump therapy, the importance of catheter change within 72 hours should be emphasized irrespective of the insulin used. 16 The purpose of this pilot study was to investigate the impact of using CSII infusion sets (Silhouette ® and Comfort™) for 5 days or more on glycemic control and the occurrence of adverse events in patients with type 1 diabetes.…”
Section: Cont Inuous Subcutaneous Insulin Infusion (Csii)mentioning
confidence: 99%